Influence of gear tooth addendum and dedendum on the helical gear optimization considering mass, efficiency, and transmission error. (December 2021) - Choi, Chanho; Ahn, Hyoungjong; Park, Young-jun; Lee, Geun-ho; Kim, Su-chul
Highlights: Optimizations were performed to determine macro geometry of gear pair. Macro geometry including tooth height was considered as design variables. Gear mass and mesh efficiency and transmission errors were considered as objectives. Three optimization cases that consider different design variables were compared. Gear macro design could be improved by considering the tooth addendum and dedendum. Abstract: In this study, the effects of the gear tooth addendum and dedendum on the optimization results for gear macro geometry design were evaluated. First, gear optimization using macro design variables was performed, excluding tooth addendum and dedendum parameters. Subsequently, the optimization, including the addendum and dedendum variables, was performed by applying the same addendum and dedendum lengths to the pinion and wheel. Finally, the gear optimization using different addendum and dedendum lengths for the pinion and wheel was completed. The gear mass, gear mesh efficiency, and transmission errors were considered as objective functions for optimization. The optimization results were min-max normalized, and the average values of the total scores were compared. The results show that the average score of the optimization considering only the main design variables was 2.7085 points and that considering the addendum and dedendum was 2.7829 and 2.8830 points, respectively, from a maximum possible score of 3.000 points. Hence, a gear macro design with better performance could be established by considering the tooth addendum and dedendum.